Response of cumin (Cuminum cyminum L.) to row spacing and seed rate - CHAUDHARY, G R (Journal of Spices and Aromatic Crops, 1999)
A field trial was conducted at Jobner (Rajasthan, India) to study the response of cumin to row spacing and seed rate. Row spacing of 15.0, 22.5 and 30.0 em recorded significantly higher mean seed yields (2.69-2.85 q/ha) over broadcast sown crop (2.45 q/ha) and were on par. Seed rate of 12 and 14 kg/ha produced significantly higher mean seed yield (3.01 and 3.00 q/ha) over 8, 10 and 16 kglha seed rate. Row spacing of 22.5 cm with 14 kg/ha seed rate gave the highest mean seed yield of 3.55 q/ha. Maximum net returns of Rs 9656 and Rs 11,0881ha with B:C ratios of 2.46 and 2.77 were obtained with the row spacing of 22.5 cm and seed rate of 12 kg/ha, respectively.